Reinterpretation of oceanic 230Th profiles based on decadal export productivity (2003–2010) - Yiming Luo (Nature Portfolio, 2017)
Abstract Understanding 230Th distributions in the global ocean is important to support and guide the use of this important radioactive nuclide in multiple aspects of oceanographic research, and this issue is now revisited. Based on estimates of export productivity (EP) over 2003–2010 and assuming 230Th scavenging at equilibrium at seven Pacific stations where linear 230Th profiles are found, an empirical equilibrium-state 230Th-scavenging versus EP correlation is established. This correlation demonstrates the relationship between 230Th-scavenging intensity and EP in the absence of advection. With this correlation, other 230Th profiles from global oceans are reinterpreted. My findings provide alternative explanations of signals carried by 230Th distributions with regard to advection, by a reassessment of the 230Th deficits in deep waters. Such an equilibrium-state 230Th-scavenging versus EP correlation provides a basis for convenient parameterization for use in 3D modeling studies of the 230Th distributions.